2019
DOI: 10.1158/1078-0432.ccr-19-0197
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA as a Clinical Test in Resected Pancreatic Cancer

Abstract: Purpose: In research settings, circulating tumor DNA (ctDNA) shows promise as a tumor-specific biomarker for pancreatic ductal adenocarcinoma (PDAC). This study aims to perform analytical and clinical validation of a KRAS ctDNA assay in a Clinical Laboratory Improvement Amendments (CLIA) and College of American Pathology-certified clinical laboratory. Experimental Design: Digital-droplet PCR was used to detect the major PDAC-associated somatic KRAS mutations (G12D, G12V, G12R, and Q61H) in liquid biopsies. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 53 publications
5
114
2
3
Order By: Relevance
“…Patients who did not harbour KRAS mutations in ctDNA but had a KRAS mutation in tissue accounted for 74.7% (74/99) (Supplementary Table 5), which indicated a little low sensitivity of 25.3% (25/99) compared with previous studies (30.0%-49.0%). 16,17 However, this is due to the impairment caused by the threshold of 0.1% AF, which we chose to avoid situations, like ageing, benign tumours and preneoplastic lesions, and better reflect the systematic tumour burden of the patients. 18 In fact, the Firefly NGS technique allowed a detection of 0.02% mutated DNA, 21 which suggested that negative results in this study did not mean no detectable ctDNA in preoperative plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who did not harbour KRAS mutations in ctDNA but had a KRAS mutation in tissue accounted for 74.7% (74/99) (Supplementary Table 5), which indicated a little low sensitivity of 25.3% (25/99) compared with previous studies (30.0%-49.0%). 16,17 However, this is due to the impairment caused by the threshold of 0.1% AF, which we chose to avoid situations, like ageing, benign tumours and preneoplastic lesions, and better reflect the systematic tumour burden of the patients. 18 In fact, the Firefly NGS technique allowed a detection of 0.02% mutated DNA, 21 which suggested that negative results in this study did not mean no detectable ctDNA in preoperative plasma.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Several studies have proved a high detection rate and potential prognostic value of ctDNA in PDAC. [14][15][16][17] However, the data regarding the complexity of exosome isolation invalidated it in other centres, and heterogeneity as well as rarity of CTCs and ctDNA restrained the application mainly in advanced patients. 18 Therefore, more stable methods and more validations are necessary before clinical application, especially for patients with early-stage PDAC who are commonly considered as resectable.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrence after curative-intent therapy is high in PDAC. One study of patients with early stage, resectable disease demonstrated 35% recurrence at 1-year follow up, while 1-year recurrence rates over 80% have been observed in patients with borderline resectable disease [ 84 , 90 ]. Early detection of recurrences is key to initiating appropriate systemic therapy.…”
Section: Current Clinical Utility Of Cfdnamentioning
confidence: 99%
“…In metastatic PC absence of KRAS mutant ctDNA was significantly associated with survival benefit of 37.5 versus 8 months (p < 0.004) (Perets et al 2018). Correspondingly, PC patients with KRAS mutant ctDNA were more likely to relapse after curative surgery than those without KRAS mutant ctDNA with deseasefree survival of 6.1 versus 16.1 months and overall survival of 13.6 versus 27.6 months (p < 0.001) (Groot et al 2019;Hadano et al 2016;Sausen et al 2015). Serial plasma testing of KRAS mutant ctDNA in advanced PC patients receiving chemotherapy allowed the monitoring of rapid changes of KRAS mutant ctDNA levels superior to CA19-9 and CEA kinetics (Kruger et al 2018).…”
Section: Genomic Alterations Of Ctdna In Pcmentioning
confidence: 96%